Profiling User Needs for Weather and Climate Information in Fostering Drought Risk Preparedness in Central-Southern Nigeria - Awolala, David Olufemi; Mutemi, Joseph; Adefisan, Elijah; Antwi-Agyei, Philip; Taylor, Andrea (Frontiers in Climate, 2022)
Weather and climate information trigger early action and facilitate disaster preparedness. Decision–driven, and people-centered weather and climate information are pivotal for effective uptake. The challenge of early responses in preparing for drought hazard is growing in the dry savannah countries. This paper analyzed user needs for weather and climate information in fostering drought risk preparedness in Central-Southern Nigeria. Stratified, snowball, and simple random samplings were used to obtain a sample of 397 respondents across the agro-ecological zones of Edo State. Structured questionnaire was used to collect household data. 8 focus group discussions and 11 key informants interviews were conducted on key economic sectors of Edo State. Results show that non-users of weather and climate information are more than users in the savannah area. Heckman probit results explained that male gender, farmers’ experience, income, and persistent incidence of erratic rainfall have more propensity to facilitate use of WCI while group membership and distance of meteorological station prevent stakeholders from developing interest in using WCI for drought preparedness and response. Multi-criteria decision-making indicated that rainfall amount, onset and cessation rainfall dates, and rainfall distributions are the most useful WCI needed by end users in their decision response plan in agriculture; rainfall intensity, rainfall cessation date, rainfall distributions, and length of dry season for water resource management while heat intensity, rainstorms, and drought alerts in the disaster risk reduction in fostering resilience towards anticipated future drought hazard. Subseasonal-to-seasonal (S2S) and medium (4-10 days) timescales are the most useful to facilitate efficient utilization and management in all the economic sectors. The users’ most preferred delivery method of receiving WCI are mobile telephone, radio, agricultural extension officers, farmers’ groups, and contact farmers/specialist for efficiency in enhancing users’ decision capacity to uptake WCI. A seamless collaborative effort in bringing scientific outputs and users' needs together through systematic efforts. NiMet should improve on its engagement with the stakeholders, the agricultural extension and planning office, water management authorities, disaster risk reduction . These policy initiatives would provide a robust collaboration for co-producing useable WCI in managing decision points and mainstream preparedness into existing decision-making apparatus in Central-Southern Nigeria.